Re-allocating taxing rights and minimum tax rates in international profit taxation - Gerhard Kempkes; Nikolai Stähler (Journal of Government and Economics, 2022)
What happens when sovereign governments coordinate their tax policies? This is an important research topic in government and economics. We focus on implications of re-allocating taxing rights away from source countries (where goods are produced) to market countries (where goods are consumed) and introducing minimum rates in international profit taxation. Utilizing a dynamic macroeconomic model, we find that, in low tax economies, the average profit tax rate will rise. On one hand, this reduces price competitiveness of firms located in these regions and, thereby, output. On the other hand, higher profit tax revenues help to reduce other taxes. Moreover, lower expected future output requires less capital in production in the long run. Firms hence invest less and (temporarily) augment dividend payments. This raises disposable income of households, who (at least temporarily) increase consumption. The opposite holds for high tax economies. In terms of welfare, low tax economies can benefit from an increase in profit taxation. Reduced “tax avoidance” and higher repatriation of firm profits only changes this picture for relatively high levels of initial profit shifting.